By His Excellency Richard Earl of Bellomont, captain general and governour in chief of His Majesties province of New-York ... A proclamation : Whereas His Sacred Majesty hath of his princely bounty been pleased in a very signal manner to extend his royal care and protection to this his province and people, during the late war ... Given at Fort William Henry the twenty third day of November, 1698 . (Printed by William Bradford, printer to the Kings Most Excellent Majesty in the city of New-York, 1698)
Requesting all citizens to swear an oath of allegiance to the Crown.